Suprasellar desmoplastic infantile astrocytoma and ganglioglioma: an institutional series report and a clinical summary of this rare tumor - Wang, Qiguang; Zhang, Yi; Zhang, Huan; Hui, Xuhui; Liu, Wenke (Frontiers in Oncology, 2025)
BackgroundDesmoplastic infantile astrocytomas/ganglioglioma (DIA/DIG) arising in the suprasellar region are extremely rare, and their clinical features, optimal management, and outcomes remain unclear. We aimed to summarize the clinical manifestations, treatment strategies, and prognosis of this rare tumor entity.Patients and methodsThis retrospective case series included 5 institutional cases and 13 literature cases of suprasellar DIA/DIGs. The clinical and radiological characteristics, therapies, and outcomes of this rare tumor were examined.ResultsOur case series comprised 2 males and 3 females, with a median age of 6 months. Three patients underwent partial resection, and 2 had subtotal resection. During follow-up, the residual tumors in 2 patients showed spontaneous regression, 1 tumor progressed, and 2 remained stable. The literature review, including our cases, yielded 18 suprasellar DIA/DIG. Of these, 10 were male and 8 were female, with a median age of 4 months (range, 1–85 months). Ten patients had solitary suprasellar tumors and 8 had multifocal lesions. Over a median follow-up of 25 months, tumor progression of the suprasellar lesions was seen in 9 patients. Notably, spontaneous regression of the suprasellar tumors occurred in 2 patients.ConclusionsDespite being WHO grade I, suprasellar DIA/DIG can demonstrate multifocal CNS disease and high risk of progression after subtotal resection. DIA/DIG should be considered in the differential diagnosis of suprasellar lesions in infants and long-term close monitoring is warranted.